Strategic planning in territorial authorities : progress and prospects : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Philosophy in Resource and Environmental Planning at Massey University - Roesler, Michael (Massey University, 1999)
Over recent years, territorial councils have had to adapt to changes in their operating environment. Many of these changes have been brought about by legislative requirements, namely the Local Government Amendment Act (1989) and the Resource Management Act (1991). Other pressures include the increasing demands from central government to adopt more market-driven philosophies and changing expectations of service provision from local communities. A small number of territorial authorities initiated strategic planning exercises in mid-1990. These exercises involved staff, councillors and local communities in what appeared to be relatively significant and distinctive processes, culminating in strategic documents. This research aims to establish whether these strategic planning exercises will he useful to TAs in their policy and decision-making processes. The research aim was influenced by a number of factors including: the lack of any substantial practical guidance and TA experience in strategic planning, the questionable nature of transferring private business sector experience to local government and the viability of private sector strategic planning in the institutional context of local government. The principal research methods used were grounded on an investigation of theory related to strategic planning, institutional context of local government, and the role of strategic planning. These aspects of theory were translated into a review of practice of three TAs. Assessments were made of TAs' institutional context, their approach to strategic planning, and their perceived role of strategic planning. These results provided the means for assessing the relationship between institutional context and the role of strategic planning. The research data was collected by conducting interviews with management staff and councillors and reviewing the strategic plans of four TAs The key research findings provide mixed messages in offering a conclusion to the research aim of establishing if strategic planning is useful to TAs in their decision-making. On one hand, strategic planning used in broad role can be an extremely useful process for improving the quality and implementation of policy decisions. However, to achieve benefits from a broader role of strategic planning, it must be accompanied by a particular institutional context. Adapting the institutional context to facilitate the use of strategic planning presents many challenges, but also highlights many old problems within local government. Strategic planning may simply provide a catalyst to find solutions to some of these old problems.
Keywords: New Zealand; Strategic planning; Local government